2022
DOI: 10.1177/09722629221110035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-service Technologies’ Attributes on Bank Customers’ Experience, Relationship Quality and Re-use Intention: Insights from a Developing Economy

Abstract: Services providers’ recent inclusion of technology-enabled mechanisms in services delivery especially in banking sector in developing economies are significantly replacing earlier human-to-human dominated pattern of bank–customer relationships. Notwithstanding glaring penetration of self-service technology applications in bank service delivery, how its attributes influence customer experience, relationship quality and reuse intention has been largely eluding research attention. Therefore, this article investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 93 publications
0
2
0
1
Order By: Relevance
“…Furthermore, the study found that the intention to use fintech significantly and positively influences a bank's sustainable performance. The study also examined the effect of the intention to use fintech on sustainable performance and the findings are consistent with the previous study of Ugwuanyi and Idoko [14]. Customer satisfaction also directly and significantly influenced the sustainable performance, and the findings are consistent with Waqas et al [41] and Junejo et al [42].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, the study found that the intention to use fintech significantly and positively influences a bank's sustainable performance. The study also examined the effect of the intention to use fintech on sustainable performance and the findings are consistent with the previous study of Ugwuanyi and Idoko [14]. Customer satisfaction also directly and significantly influenced the sustainable performance, and the findings are consistent with Waqas et al [41] and Junejo et al [42].…”
Section: Discussionsupporting
confidence: 87%
“…These researchers found that customers were more likely to re-use a service if they were satisfied with it. This argument was given additional credence by Ugwuanyi and Idoko [14], who demonstrated that the characteristics of self-service technologies considerably impacted the overall banking experience and, consequently, the re-use intentions.…”
Section: Customer Satisfaction and Sustainable Performance Of Banksmentioning
confidence: 98%
See 2 more Smart Citations
“…Một trong những khung lý thuyết phổ biến để giải thích cho ý định mua hàng và/hoặc hành vi mua hàng trong mối quan hệ giữa khách hàng và công ty là mô hình chất lượng mối quan hệ (Relationship Quality -RQ). Có nhiều bằng chứng cho thấy chất lượng mối quan hệ có tác động tích cực đến quá trình ra quyết định của khách hàng như: Ý định mua hàng (Cannière và cộng sự, 2010), ý định sử dụng lại sản phẩm dịch vụ (Ugwuanyi & Idoko, 2022), hành vi gắn bó (Fernandes & Pinto, 2019), gia tăng lòng trung thành của khách hàng (Supriyanto và cộng sự, 2021), và ý định mua chéo sản phẩm dịch vụ (Vyas và cộng sự, 2018). Một lý thuyết khác cũng được sử dụng để giải thích ý định/hành vi của khách hàng là Lý thuyết về hành vi có kế hoạch (The Theory of Planning Behaviour -TPB) (Ajzen, 1991(Ajzen, , 2002Armitage & Connor, 2001).…”
Section: ảNh Hưởng Của Chất Lượng Mối Quan Hệ đốI Với Hành VI Mua Chéounclassified